PERBANDINGAN MOTIVASI PEMBELAJARAN PJOK DI LAPANGAN INDOOR DAN OUTDOOR SMA METODHIS 6 MEDAN - Rizki Bastanta B. Manalu; Aser Paul Nainggolan; Mos Devan Tarigan (JURNAL CURERE, 2022)
This study aims to determine the differences in learning motivation of PJOK between study groups in indoor and outdoor fields at Methodist 6 Senior High School Medan. Class XI students of SMA Methodis 6 Medan are the population of this comparative study. The sample of this study consisted of 64 students of class XI SMA Methodis 6 Medan who were selected using the Slovin formula and the total population was 74 students. Using Google forms and a Likert scale, the research instrument uses a learning motivation questionnaire that was previously used in the study. With the help of SPPS Statistics Version 21, descriptive statistical tests and independent tests were used to assess the research data. Based on the results of the study, it is known that there is a significant difference between learning motivation in the PJOK learning group in the indoor and outdoor fields of class XI students of SMA Methodist 6 Medan. It is known that the significant value (0.000) is smaller than the Alpha value (α 0.05), which means that (0.000) < (0.05), there is a t-count value of 7,022 which is higher than t table 1.992, so students tend to be more motivated when PJOK learning in the outdoor field. Because most students, according to research, like to study in the open field, students tend to be more motivated when studying PJOK there. Due to the lack of friends to chat with and boredom with PJOK activities during the COVID-19 pandemic, some children lack motivation to study in an indoor environment.